Complaint Procedure for Failure to Ensure Accessibility for People with Special Needs - Cebera, Agata (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The subject of the study is the system of legal instruments aimed at ensuring the fulfillment of the obligations arising from the system act on ensuring accessibility. The article describes, among others complaint procedure with an assessment of its effectiveness.